Who is a Feminist? What Nigerians Say - OSONDU-OTI, Adaora (The Gender Truth Journal, 2026)
Feminists have been fighting for gender equality for over 100 years, and feminism has gained significant attention all over the world. Yet the word feminist is not only controversial but also comes with several negative connotations. It is a word not many men want to hear, and even women do not want to be identified with because of the negative stereotypes and misconceptions associated with feminists. For example, a 2018 YouGov poll in the UK with a sample size of 2010 adults in Great Britain found that eight out of ten people who participated in the survey agreed that men and women should be treated equally in every way, but still did not want to be identified as feminists. In Germany, only 8percent of women, when asked if they were feminist, said yes. This makes one ponder the problem with the word feminist, and whether the issue of people distancing themselves from the word is the same across the world. This study’s primary aim is to gain insight on Nigerian’s interpretation of who a feminist is. It will determine whether Nigerians’ understanding of feminism aligns with the dictionary definition of the term and what causes the negative labels that make Nigerians (men and women) avoid the term or prefer not to be identified as a feminist. Through an online survey where over 250 Nigerians responded to a questionnaire, this study revealed Nigerians’ idea of feminism and who a feminist is. While the majority (85percent) of the respondents support equal rights and opportunities for women and men, close to 50 percent of the respondents avoid being called a feminist and do not identify as feminists. The respondents see feminism as alien and associate it with the westernization of Nigerian culture. To 85 percent of the respondents, feminists are generally bitter and uncontrollable women who deviate from the cultures and traditions of the country. In view of the findings above, this paper then recommends a reorientation of Nigerian men and women for a better understanding of feminism and who a feminist is. Proper education about the traditional idea behind feminism would no doubt help in changing the negative labels of a feminist as an alien, deviant, bitter, aggressive, and uncontrollable woman who cannot live under/with a man. Feminists aim to primarily advocate equal rights for men and women, and do not deserve negative labels under the guise of culture and religion.The women feminists not properly informed about feminism should be enlightened and not condemned.